Long-term outcomes and prognostic factors affecting survival after pulmonary metastasectomy in solid tumors of childhood: A single center experience - Vivek Samuel Gaikwad; Rikki Rorima John; Reka Karuppusami; Tarun John K. Jacob; Leni Grace Mathew; Jujju Jacob Kurian (Wolters Kluwer Medknow Publications, 2022)
Introduction: This study assessed the long-term survival and the prognostic variables affecting survival following pulmonary metastasectomy (PM) secondary to childhood solid tumors. Materials and Methods: A retrospective analysis was done on 22 children who underwent PM for solid tumors between January 2007 and February 2020. The overall survival (OS) and event-free survival (EFS) at the end of the study period were noted. Tumor histology, completeness of resection, disease-free interval, laterality, location, number, and size of lung nodules were assessed for their significance in contributing to survival. Results: High-grade osteosarcoma (54.5%), followed by Wilms' tumor (18.2%), was the most common histological types. Unilateral nodules (59.1%) situated in a peripheral, sub-pleural location (91%) were the most common presentation. Pleural extension was noted in 12 (54.5%) patients. Synchronous pulmonary metastases were noted in 12 (54.5%) patients. Two developed metastases while undergoing chemotherapy and eight after the completion of therapy. The EFS and OS were both 31.8% at a median follow-up of 15.5 months (range 3-129 months). The median time required for an event to occur was 4 months (95% confidence interval [CI]: 1.4, 6.6 months) and median post-PM survival interval was 17 months (95% CI: 6.6, 27.4 months). Significant association was noted between preoperative tumor response to chemotherapy (P = 0.002) and survival. Conclusion: PM can improve survival in a select group of children with metastatic solid tumors. Favorable tumor response to chemotherapy was found to be a significant prognostic factors influencing survival.